Mauritius : Staff Report for the 2014 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2014)
This 2014 Article IV Consultation highlights that with subdued international prices, inflationary pressures in Mauritius declined in 2013, despite the public sector wage increases. The unemployment rate was unchanged compared with 2012 at 8 percent. Credit to private sector growth remained robust. On the external front, the current account deficit widened to almost 10 percent of GDP in 2013. The reserve cover of imports of goods and services stayed constant at 4 1\2 months with the Bank of Mauritius accumulating additional net international reserves. The structural primary deficit was broadly unchanged relative to 2011.